PRELIMINARY RESULTS OF MODELING OF LIGHT CURVES OF WW AND - Zola, S. (Одеські астрономічні публікації, 2017)
In this work we present the preliminary results of modeling of Olson’s lybv light curves of an Algol-type binary WW And. A model of a binary star containing an accretion disk around the primary star is deployed. We present a solution for the mass ratio fixed at q=0.20.